Analyzing the Students’ Obstacles in English Reading Comprehension at Senior High School - Rohmawati, Laili; Hasbullah; Abd. Rahman (Institut Agama Islam Negeri Palopo, 2025)
This study aims to identify the obstacles faced by grade 11 students at MAN Sorong SP 4 in comprehending English reading texts. Employing a mixed-methods approach, data were collected through a 4-point Likert scale questionnaire completed by 20 students and semi-structured interviews with 5 students and 1 English teacher. The instrument covered four key areas: vocabulary mastery, motivation, media preferences, and teacher support. Results revealed that 76% of students struggled with vocabulary, 71% lacked effective reading strategies such as skimming and inference, and 64% had difficulties understanding text structures. Additionally, 60% of students demonstrated low motivation toward academic reading, although they showed interest in English content through social media. Interview findings supported the quantitative data, indicating students' reliance on dictionaries, absence of explicit reading strategy instruction, and low confidence in dealing with complex texts. The study recommends an instructional approach that integrates reading strategies, vocabulary development, and educational digital media to enhance students’ holistic reading comprehension skills.